For A Fairer Legislative Regulation of the Jordanian Personal Status Law No. 15 of 2019: Custody as a Case Study - Sana J Hunaiti (دراسات: علوم الشريعة والقانون, 2021)
The Jordanian Personal Status Law has an effective role in achieving justice and the best interest of the child subject to custody, has the utmost attention of the Jordanian legislative institutions and the Jordanian judicial institution, and that is in the hope of achieving the highest levels of justice for the child, and the guardian, which ultimately is in the best interest of the child. This study included the legal articles related to the custody in the Jordanian Personal Status Law No. (15) of 2019 CE. The descriptive, inductive and analytical approaches were used to suggest an alternative legislative regulation for some legal articles. The researcher concluded that the Jordanian legislator has done well in legislation in many legal articles, such as placing restrictions and guarantees in some legal articles to achieve the interests of the child. Since these legal articles are formulated by humans, there must have been a legislative space in some of them that would disrupt the implementation of the concept of justice in them, so the researcher referred to that legislative space by suggesting ways to fill that space according to the subject that the legal article talks about, hoping to achieve the best interest of the child. Therefore, the Jordanian legislator recommends that the proposed legislative regulations should be considered and adopted, such as canceling the text related to the fall of custody in the situation of the marriage of the custodian.